Blood Pressure Profiles in Infants With Hypoxic Ischemic Encephalopathy (HIE), Response to Dopamine, and Association With Brain Injury - Pazandak, Christine; McPherson, Christopher; Abubakar, Maryam; Zanelli, Santina; Fairchild, Karen; Vesoulis, Zachary (Frontiers in Pediatrics, 2020)
Objective: To describe mean arterial blood pressure (MABP), responsiveness to dopamine, and relationship to brain injury in infants with moderate/severe hypoxic-ischemic encephalopathy (HIE) undergoing therapeutic hypothermia (TH). We hypothesized that, when utilized, dopamine would rapidly and effectively increase MABP in treated patients. Methods: Continuous arterial blood pressure measurements were prospectively recorded from infants with moderate/severe HIE undergoing TH in a multi-institutional cohort from 2010-2018. Treatment with dopamine was at the discretion of the medical team for hypotension/hypoperfusion. MABP values of treated infants were compared to those obtained at an equivalent time period in control infants receiving TH but not dopamine (24h after birth). MRI was obtained per unit protocols and included T1/T2/DWI sequences. Injury was classified as no injury/mild injury or moderate/severe injury using a standardized scoring system. Seizures were confirmed with conventional EEG. Results: Eighteen infants were treated with dopamine and were similar to untreated controls (n = 36) with the exception of lower cord gas pH (6.92 ± 0.2 vs. 7.07 ± 0.2, p<0.05). Dopamine was initiated at a mean of 24 hours after birth. MABP was significantly lower in the dopamine group at the start of therapy (39.9 ± 2.0 vs. 49.1 ± 1.3, p < 0.01) and one hour later (44.3 ± 2.0 vs. 49.8 ± 1.1, p < 0.05). However, after 9 hours of treatment, dopamine increased the MABP by an average of 9 mmHg and MABP values were similar to untreated controls for the remainder of the observation period. There were no significant differences in rates of seizures, brain injury, or death. Conclusion: Neonates with moderate/severe HIE treated with dopamine during TH had MABP significantly lower than controls. The majority of infants responded to dopamine monotherapy following adequate volume resuscitation. An association between requirement for dopamine and severity of brain injury was not detected.